Thinking fragments: Psychoanalysis, feminism, and postmodernism in the contemporary west - Flax, Jane (University of California Press, 1990)
Thinking Fragments provides a brilliant critique of psychoanalytic, feminist, and postmodern theory. Examining the writings of Freud, Winnicott, Lacan, Chodorow, Irigaray, Derrida, Rorty, and Foucault, among others, Flax conducts a "conversation" among psychoanalysts, feminist thinkers, and postmodern theorists, evaluating the ways in which each group of thinkers succeeds in coming to terms with crises in contemporary Western culture. As she analyzes each theory in turn, the others are used to identify and interrogate its gaps and omissions. The result is a postmodern text of intertwined ideas, devoid of clear beginnings, endings, conclusions. Flax addresses the question, "how is it possible to theorize in the contemporary West?" With the demise of objective notions of truth, knowledge, self and power, intellectuals have devised these new modes of thinking which both reflect and contribute to the uncertainties of the contemporary West. Each also addresses at least one aspect of what has become most problematic to modern individuals: How to come to terms with self, gender, knowledge and power without resorting to concepts that stress objectivity, universal knowledge, and a unitary self. Flax finds that neither psychoanalysis, nor feminism, nor postmodernism is adequate to the task for which it was conceived. Each can illuminate certain aspects of problems of self, gender, knowledge, and power, but none is sufficient on its own. In fact, each incorporates characteristic blindnesses rooted in part in the very difficulties it addresses. Despite their failures, Flax concludes that these modes of theorizing are our best tools thus far, compelling us to use them even while we grapple with the problems they raise. Thinking Fragments is a wide-ranging study that will elicit much discussion and debate. It is an essential text for social scientists and humanists alike, as well as anyone else who thinks about how to "do" theory in the contemporary West.
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; occident; postmodernisme; premier cycle; psychanalyse; périodes historiques; ressource en ligne; sciences; sciences humaines

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles

Feminism/postmodernism - Nicholson, Linda J. (Routledge, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis